Investigating the underlying mechanisms of temperature-related skin diseases in Atlantic salmon, Salmo salar L., as measured by quantitative histology, skin transcriptomics and composition - Jensen, Linda; Boltana, Sebastian; Obach, Alex; McGurk, Charles; Waagbo, Rune; MacKenzie, Simon (Journal of Fish Diseases, 2015)
Skin integrity is recognized as of vital consideration for both animal welfare and final product quality of farmed fish. This study examines the effects of three different rearing temperatures (4, 10 and 16°C) on the skin of healthy Atlantic salmon post-smolts. Changes in skin condition were assessed by the means of skin composition analyses, quantitative histology assessments and transcriptome analysis. Level of protein, vitamin C and vitamin E was significantly higher at 16°C compared with 4°C. Quantitative histology measurements showed that the epidermal thickness decreased from low to high temperature, whereas the epidermal area comprising mucous cells increased. The difference was only significant between 4 and 16°C. Both high and low temperature exhibited significant changes in the skin transcriptome. A number of immune-related transcripts responded at both temperatures. Contrary to well-described immunosuppressive effects of low water temperature on systemic immunity, a subtle increase in skin-mediated immunity was observed, suggesting a pre-activation of the mucosal system at 4°C. Upregulation of a number of heat-shock proteins correlating with a decrease in epidermal thickness suggested a stress response in the skin at high temperature. The results demonstrate distinctive temperature-related effects on the skin of Atlantic salmon.